MODELING AND ASSESSMENT OF RENEWAL LEVEL OF PERSON’S COMPETENCE POTENTIAL - Городянська, Лариса В. (Journal of Strategic Economic Research, 2024)
The existing methods and techniques of modeling and operational assessment of the renewal level of a person’s competence potential requires improvement to develop the assessments’ results of objectivity and professional orientation. Therefore, the purpose of the research is to a modeling and develop the method of quantitative assessment of the renewal level of a person’s competence potential according to their types. The methodology is based on the application of analysis, synthesis, multidimensional modeling methods, dialectics, as well as systemic, logical, structural-functional, comparative, abstract-logical, and other approaches. The functional model of the evaluation system, the factor-criterion model, the algorithm and the method of quantitative assessment of the types of the renewal level of the human competence potential, developed in the study, differs from others in that the competence of a person for each factor is determined according to the conditions of the qualitative factor-criterion model as a sum of competencies according to the criteria characterizing this factor. The model factors are the components of the basic, key, or other competencies of a person. The model criteria are the list of skills, abilities, attitudes, creative skills, and other personal and professional qualities that are evaluated based on the structure of each competency. The examples contains the effect of modeling, and the method of a quantitative assessment of the person’s competence potential level renewal. The practical application of the modeling and the method of a quantitative assessment of the renewal level of the person’s competence potential, which is proposed to use online interactive platforms, electronic testing, and artificial intelligence, is important for operational, objective and comprehensive assessment and measurement of a person’s professional qualities. The obtained results of the method of assessments of scientific studies and quantitative assessment of the types of the renewal level competence potential of the human allows the enterprise to use available intellectual potential by holding attestation and re-attestation of personnel. Results also allows to conduct objective area knowledge assessment with job applicant’s by interviewing and holding tenders for vacancy replacements.